7 cajas - Maneglia, Juan Carlos; Franco, Celso; Sosa, Víctor; González, Lali, 1986-; García, Nico; Paletita; Zelada, Juan; Careaga, Richard; Villalba, Fran (Maneglia Schémbori Realizadores, 2012)
"It's Friday in Asunción and the temperature is 40°C. Víctor, a 17 year-old [delivery] boy, dreams of becoming famous and can't take his eyes off the TV set in Mercado 4. He's offered the chance to deliver 7 boxes without knowing what they contain in exchange for 100 dollars. But what sounded like an easy job soon gets complicated. Something in the boxes is highly coveted. Víctor and his persecutors find themselves caught up in a crime they know nothing about."--